Perception Matters: The Influence of School Ethnic Racial Context on Ethnic Racial Identity Development for Black Adolescents - Amirah Saafir; Sandra Graham (Behavioral Sciences)
In the current study, latent growth curve modeling is used to explore growth in ethnic–racial identity (ERI) commitment from 9th to 12th grade as a function of two aspects of the school ethnic–racial environment—perceived representation among peers and perceived discrimination from peers. The participants included 237 students that self-identified as African American (Mage = 14.7; 50% female). The results showed that perceiving more Black peers at school buffered the negative impact of racial discrimination from peers on ERI commitment. Further, the positive impact of perceived representation remained significant even after controlling for other markers of school ethnic–racial context including objective representation and school ethnic–racial diversity. The findings have implications for the environmental factors that support ERI development as well as how we study and conceptualize the influence of the school ethnic–racial environment.